Characteristics of patients treated for active lower gastrointestinal bleeding detected by CT angiography: Interventional radiology versus surgery. Issue 120 (November 2019) - Pannatier, Megan; Duran, Rafael; Denys, Alban; Meuli, Reto; Zingg, Tobias; Schmidt, Sabine
Highlights: No consensus about the first treatment of active lower intestinal bleeding exists. Actively bleeding patients treated by angiography are older than surgical patients. Hemodynamic values of interventional patients do not differ from surgical patients. Angioembolisation should be the first choice in active lower intestinal bleeding. Abstract: Purpose: To determine radiological or clinical criteria guiding treatment decisions in active lower gastrointestinal bleeding (LGIB). Materials and methods: We consecutively and retrospectively included all patients admitted to our emergency department for acute LGIB proven by CT angiography (CTA) from 2004 to 2017. Patients were divided into two groups depending on whether they first underwent interventional radiological (IR) or surgical treatment. Two radiologists reviewed CTA and angiographic images. Patients' hemodynamic and clinical parameters, delay between imaging and treatment, procedure characteristics, and outcomes were investigated to detect differences between the two groups. Results: Initial management consisted of IR in 62 cases (70.5%) and surgery in 26 (29.5%). IR cases were older than surgical cases (74.3 vs 64.3y, p = 0.014). Baseline hemodynamic parameters were similar between the two groups. For colonic bleeding sources, the delay between CTA and IR was shorter than between CTA and surgery (p = 0.027), while there was a trend towards a shorter delay for all LGIB taken together (p = 0.061). In cases with hematochezia or melena, IR was more frequently performed than surgery (p = 0.001). Surgical cases showed higher base excesses (p = 0.039) and lactate levels (p = 0.042) after treatment compared with IR cases. Length of hospital stay was similar between the two groups (p = 0.728). During angiography, 41 (66%) cases were embolized. Complications occurred in three cases after IR (7%) and in five after surgery (19%). Conclusion: Initial management of active LGIB revealed by CTA (i.e. IR versus surgery), may depend on age and clinical signs, rather than hemodynamic parameters.